Understanding Crime and Place : a methods handbook - Groff, Elizabeth (Elizabeth R.); Haberman, Cory P., 1985- (Philadelphia: Temple University Press, 2023)
"This book instructs students and scholars in foundational methods, measurements, theories, and standard practices in the study of preventing and predicting crime through geographies and place-based research methodologies. The chapters by leading experts include exercises and walkthroughs"--
Includes bibliographical references and index.
Keywords: Criminology -- Research -- Statistical methods; Crime prevention -- Research -- Statistical methods; Criminal statistics -- Research; Crime -- Environmental aspects